Pengaruh Orientasi Kognitif Terhadap Kesalahan Pelaporan dengan Sistem Pengendalian Manajemen sebagai Variabel Moderasi - Ferlyani Adilla Haque; Grace Tianna Solovida (AKSES: Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this study was to determine the effect of cognitive orientation on misreporting with the management control system as a moderating variable. This study used a sample of 67 postgraduate Management Master students at Pancasakti University, Tegal. The sampling technique in this study used a non-probability sampling method, namely purposive sampling. Data analysis was performed using 2X2 analysis of variance (ANOVA) with the help of SPSS 16 software. The test results show that the management control system has a positive and significant effect on misreporting. Cognitive orientation has a positive and significant effect on misreporting.